2021
DOI: 10.1111/jcal.12600
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing distance learning of science—Impacts of remote labs 2.0 on students' behavioural and cognitive engagement

Abstract: Background: With the increasing popularity of distance education, how to engage students in online inquiry-based laboratories remains challenging for science teachers. Current remote labs mostly adopt a centralized model with limited flexibility left for teachers' just-in-time instruction based on students' real-time science practices.Objectives: The goal of this research is to investigate the impact of a non-centralized remote lab on students' cognitive and behavioural engagement.Methods: A mixed-methods desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…As an example of practical applications, digital twins delivered through Telelab have provided intuitive user interfaces for remotely accessing science laboratories during the COVID-19 pandemic, resulting in improved student engagement and learning in online environments. In a teacher’s own words, “In real labs, I ask students to do free exploration before giving specific instructions on where to observe and what to analyze. Then we share, as a whole class, what we find.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…As an example of practical applications, digital twins delivered through Telelab have provided intuitive user interfaces for remotely accessing science laboratories during the COVID-19 pandemic, resulting in improved student engagement and learning in online environments. In a teacher’s own words, “In real labs, I ask students to do free exploration before giving specific instructions on where to observe and what to analyze. Then we share, as a whole class, what we find.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…The challenges in adopting remote science laboratories in both higher education and schools mentioned by Cooper (2005) decades ago are still being experienced. One of the specific challenges highlighted by Sung et al (2021) in the use of remote laboratories is the limited interaction among the learners and the instructors. Accordingly, in the study, Sung et al (2021) developed a remote laboratory system that enabled teachers and learners to interact in real time by synchronizing the student-instructor-machine interactions.…”
Section: Computer-based Technologies Used To Facilitate Practical Wor...mentioning
confidence: 99%
“…One of the specific challenges highlighted by Sung et al (2021) in the use of remote laboratories is the limited interaction among the learners and the instructors. Accordingly, in the study, Sung et al (2021) developed a remote laboratory system that enabled teachers and learners to interact in real time by synchronizing the student-instructor-machine interactions. In their analysis, Sung et al (2021) observed that the resultant interactions gave learners a form of telepresence that translated into enhanced learning gains.…”
Section: Computer-based Technologies Used To Facilitate Practical Wor...mentioning
confidence: 99%
“…Asynchronous learning activities benefitted students who shared devices, living spaces, and the Internet with others or those who had unanticipated obligations owing to the pandemic. It has been established that multimedia movies can be a highly effective teaching tool for delivering content to students if cognitive load, student engagement, and active learning have been all considered when creating videos (Sung et al, 2021).…”
Section: Delivery Modementioning
confidence: 99%